Determination of loading in the lower limb joints during step-forward lunge in fencing - Blazkiewicz, M.; Borysiuk, Z.; Gzik,M. (Acta of Bioengineering and Biomechanics, 2018)
Purpose: Sabre is one of the three disciplines in fencing, characterised by the use of a lightweight cutting weapon to score hits on an opponent while maneuvering for position with dynamic footwork. The aim of this study is concerned with the estimation of the load applied to the lower extremities during a step-forward lunge. Methods: The study group comprised sixteen subjects from ASA club. Examinations of kinetic parameters of analyzed movement were carried out using Vicon system, Kistler plates and the equipment designed to measure joint torques in isometric conditions. Results: Maximal value of the vertical component of the ground-reaction-force generated by the lead leg is significantly higher than the one recorded in the rear leg. The maximal value of hip flexion torque of lead leg in dynamic conditions significantly exceeds the value for this joint recorded in isometric conditions. The maximal value of knee flexion of rear leg in dynamic conditions significantly exceeds the value obtained in the isometric conditions. In general, the sequence of the joint loading from the highest to the lowest is as follows: hip, knee, ankle. Conclusions: The comparative analysis of the torques generated by the muscles in isometric and dynamic conditions provides an adequate tool for the assessment of the characteristics of the muscle effort. Therefore, it defines the structure of movement patterns in saber, from the kinetics` point of view, in the process of improving fencing footwork.